1984
DOI: 10.1111/j.1423-0410.1984.tb00102.x
|View full text |Cite
|
Sign up to set email alerts
|

Serology and Genetics of an MNSs‐Associated Antigen Dantu

Abstract: Dantu, a previously undescribed low-incidence red cell antigen, is inherited as a Mendelian dominant character. The Dantu antigen is associated with very weak s antigen, protease resistant N antigen and either very weak or no U antigen. Two of the propositi had previously been shown to have an unusual hybrid MNSs sialoglycoprotein, and it is probably this which carries these unusual N, s and U antigens as well as the Dantu antigen. A study of the family of one propositus suggests, by conventional genetics, tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 9 publications
0
23
0
Order By: Relevance
“…The Dantu antigen has recently been shown to be associated with an unusual protease-resistant N antigen (Contreras et al, 1984). N3 has been shown to agglutinate cells of the Dantu/MS, Dantu/Ms and Dantu/Mu types, presumably due to recognition of the "N' antigen borne by the Dantu sialoglycoprotein molecule (Moores, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…The Dantu antigen has recently been shown to be associated with an unusual protease-resistant N antigen (Contreras et al, 1984). N3 has been shown to agglutinate cells of the Dantu/MS, Dantu/Ms and Dantu/Mu types, presumably due to recognition of the "N' antigen borne by the Dantu sialoglycoprotein molecule (Moores, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…Anti-Dantu belongs to the group of antibodies against low-frequency antigens that occur frequently in human sera under conditions of increased erythrocyte destruction [13]. There is evidence that the formation of some of these antibodies might be triggered by cryptic structures in normal glycoproteins that are covered by carbohydrate chains [S, 421. Since the Dantu antigen appears to be located in a carbohydrate-free region of the hybrid molecule, the hypothesis mentioned above does not provide an explanation for the frequent occurrence of anti-Dantu.…”
Section: Discussionmentioning
confidence: 99%
“…(genotype DantulMu) described previously [I, 2, 12, 131 and an additional Black donor (genotype DantulMs). Some studies were also performed on a pool of Dantu-positive erythrocytes from ten unrelated individuals detected in Chicago or Houston or by several colleagues (T. Stout, Vancouver; M. Contreras, London [13]; K. Skradsky, Minneapolis). Two human anti-S sera containing anti-Dantu and an anti-Dantu made by a pregnant woman (H.P.…”
Section: Ma Terialsmentioning
confidence: 99%
“…The membranes of the cells contain a hybrid 8-a form of SGP of which two variants, Ph and NE, are known [7]. The antigens be sides Dantu encoded by the Dantu gene complex are variable strength M and N, no or very weak U and an unusual form of In this paper, studies with the blood of a family of mixed ethnic origin from Cape Town are reported.…”
mentioning
confidence: 99%
“…Dantu is a low-frequency red cell anti gen of the MNSs system found so far mainly in people of Negro origin [7]. The membranes of the cells contain a hybrid 8-a form of SGP of which two variants, Ph and NE, are known [7].…”
mentioning
confidence: 99%